Analysis of fluoride concentration in mother's milk substitutes Análise da concentração de flúor em substitutos do leite materno - Ana Valéria Pagliari; Suzely Adas Saliba Moimaz; Orlando Saliba; Alberto Carlos Botazzo Delbem; Kikue Takebayashi Sassaki (Sociedade Brasileira de Pesquisa Odontológica, 2006)
The aim of the present study was to determine the fluoride concentration in some brands of mother's milk substitutes and evaluate the possibility of developing dental fluorosis by consuming these products. The products, all powdered, were divided into 3 groups: infant formulae (group I, n = 7), milk-based (group M, n = 8) and soy-based (group S, n = 3). Samples from 3 cans of different batches of each brand were reconstituted in deionized water and analyzed using the specific electrode method, after hexamethyldisiloxane (HMDS) facilitated diffusion. The fluoride content (mg F/L) of the products ranged from 0.044 to 0.326 (I), 0.014 to 0.045 (M) and 0.253 to 0.702 (S). There was significant difference in the fluoride content of cans from distinct batches (p < 0.05) in most of the brands. The reconstitution of all products in water with optimal fluoride concentration for consumption during the mineralization phase of the primary teeth could result in daily fluoride intake above 0.07 mg F/kg body weight/day. Therefore, the consumption of these products, especially when reconstituted with optimally fluoridated water, could increase the risk of developing dental fluorosis. Este estudo teve como objetivos determinar os teores de flúor de algumas marcas comerciais de substitutos do leite materno e avaliar a possibilidade de desenvolvimento de fluorose dentária com o consumo destes produtos. Os produtos, todos em pó, foram divididos em três grupos: fórmulas infantis (grupo F, n = 7), leite (grupo L, n = 8) e leite de soja (grupo S, n = 3). As amostras de pó de três latas de lotes diferentes de cada marca comercial foram reconstituídas em água deionizada e analisadas pelo método eletrodo específico, após difusão facilitada por hexametildisiloxane (HMDS). O conteúdo de flúor (mg F/L) dos produtos variou de 0,044 a 0,326 (F), 0,014 a 0,045 (L) e 0,253 a 0,702 (S). Houve diferença significativa (p < 0,05) entre o conteúdo de flúor de latas de lotes diferentes do mesmo produto na maioria das marcas comerciais analisadas. A reconstituição de todos os produtos em água com concentração ótima de flúor, para o consumo de crianças na faixa etária de formação dos dentes decíduos, pode resultar em quantidades diárias de ingestão de flúor superiores a 0,07 mg F/kg peso/dia. Portanto, o consumo desses produtos, principalmente quando reconstituídos em água fluoretada poderia aumentar o risco de desenvolvimento de fluorose dentária.